A Heuristic Method for Performance Evaluation of Learning in an Intelligent Tutoring System - Mishra, Kiran; Mishra, R. B. (INFOCOMP Journal of Computer Science, 2010)
Evaluating student’s performance is one of the important actvities in intelligent tutoring system. This paper presesnts learning strategy for study and a heuristic method for performance evaluation of learning of student in intelligent tutoring system.A course has been divided in to different interlinked courseware.The method is based on the number of attempts with and without hint for success in a courseware and student’s performance in a courseware.Grading such as average,good,excellent has been assigned to the student based on his performance value index.A comparative view of different methods has been presented based on some characteristics such as: computing model,evaluation parameter and evaluation measure.A graphical view of comparison has also been presented